Purification and functional motifs of the recombinant ATPase of orf virus - Lin, Fong-Yuan; Chan, Kun-Wei; Wang, Chi-Young; Wong, Min-Liang; Hsu, Wei-Li (Protein expression and purification, 2011)
Our previous study showed that the recombinant ATPase encoded by the A32L gene of orf virus displayed ATP hydrolysis activity as predicted from its amino acids sequence. This viral ATPase contains four known functional motifs (motifs I–IV) and a novel AYDG motif; they are essential for ATP hydrolysis reaction by binding ATP and magnesium ions. The motifs I and II correspond with the Walker A and B motifs of the typical ATPase, respectively. To examine the biochemical roles of these five conserved motifs, recombinant ATPases of five deletion mutants derived from the Taiping strain were expressed and purified. Their ATPase functions were assayed and compared with those of two wild type strains, Taiping and Nantou isolated in Taiwan. Our results showed that deletions at motifs I–III or IV exhibited lower activity than that of the wild type. Interestingly, deletion of AYDG motif decreased the ATPase activity more significantly than those of motifs I–IV deletions. Divalent ions such as magnesium and calcium were essential for ATPase activity. Moreover, our recombinant proteins of orf virus also demonstrated GTPase activity, though weaker than the original ATPase activity.